Ulnar motor study to first dorsal interosseous: Best reference electrode position and normative data - AKYÜZ, GÜLSEREN DERYA (WILEY-BLACKWELL, 2015)
Introduction: Reference electrode position affects nerve conduction study results. This study was undertaken to determine the optimal reference electrode position for ulnar motor recording from the first dorsal interosseous (FDI) muscle and to develop normative data. Methods: Fifty-one subjects were tested using reference electrode positions on the thumb, index, and little fingers. Latencies were compared with a needle recording from the FDI. Analysis was performed to determine the surface placement that most closely matched the needle recording latency. A normative database was then derived on 100 healthy subjects. Results: Placing the reference electrode on the thumb yielded results closest to the gold standard needle recording latency. The 97th percentile (upper limit of normal) for latency was 4.0 ms. The 3rd percentile values (lower limit of normal) for amplitude were 9.0 mV for men and 9.3 mV for women. Conclusions: The reference position on the thumb yields latencies that most closely approximate needle recording. Normative data are presented. Muscle Nerve52: 231-233, 2015
Keywords: deep palmar branch of the ulnar nerve; electrodiagnosis; first dorsal interosseous muscle; nerve conduction study; ulnar nerve; NERVE-CONDUCTION; MUSCLE